MULTILINGUAL EDUCATION IN THE REPUBLIC OF KAZAKHSTAN - Умиталиева, Айгирим (Вестник ЗКУ, 2022)
The article is devoted to the actual problems of multilingualism, multilingual education in the conditions of a multicultural tolerant environment and the mechanism of training multilingual personnel in modern Kazakhstan. Currently, the priority direction in the socio-economic development of the Republic of Kazakhstan is the development of three languages by Kazakhstan people. In this regard, Kazakhstan is completely modernizing the education system and introducing a policy of trilingualism in the educational process. Along with this, the main directions of the trilingualism policy are analyzed and data on its implementation in practice are provided. The years of development of sovereign Kazakhstan show that multilingualism in society not only does not infringe on the rights and dignity of the Kazakh language, but also creates the necessary conditions for its development and progress. The article also discusses the concepts of language acquisition by modern youth, the manifestation of these concepts in other countries. The results of the study are based on sociolinguistic data that were conducted in all regions of the country.